Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x+3\right)\left(x^2-3x+9\right)-x\left(x-1\right)\left(x+1\right)=27\)
\(\Leftrightarrow x^3+27-x\left(x^2-1\right)=27\)
\(\Leftrightarrow x^3+27-x^3+x=27\)
\(\Leftrightarrow27+x=27\)
\(\Leftrightarrow x=0\)
#H
xy -1 = 3x+5y+4
<=> xy -3x-5y=5
<=>xy-3x-5y+15=20
<=>x(y-3)-5(y-3)=20
<=> (x-5)(y-3) =20
Vì x,y E Z và (x-5)(y-3)=20
=> (x-5),(y-3) E Ư(20)={+1;+2;+4;+5;+10;+20}
Ta có bảng sau
x-5 -20 -10 -5 -4 -2 -1 1 2 4 5 10 20
y-3 -1 -2 -4 -5 -10 -20 20 10 5 4 2 1
x -15 -5 0 1 3 4 6 7 9 10 15 25
y 2 1 -1 -2 -7 -17 23 13 8 7 5 4
Do x,y E Z => (x;y) E { (-15;2);(-5;1);(0;-1);(1;-2);(3;-7);(4;-17);(6;23);(7;13);(9;8);(10;7);(15;5);(25;4)} (thỏa mãn)
KL:...
\(8xy^3+x\left(x-y\right)^3\)
\(=x\left[8y^3+\left(x-y\right)^3\right]\)
\(=x\left[\left(2y\right)^3+\left(x-y\right)^3\right]\)
\(=x\left(2y+x-y\right)\left[\left(2y\right)^2-2y\left(x-y\right)+\left(x-y\right)^2\right]\)
\(=x\left(x+y\right)\left(4y^2-2xy+2y^2+x^2-2xy+y^2\right)\)
\(=x\left(x+y\right)\left(7y^2+x^2-4xy\right)\)
x2+(2a+b)xy+2aby2
=x2+2axy+bxy+2aby2
=(x2+bxy)+(2axy+2aby2)
=x(x+by)+2ay(x+by)
=(x+by)(x+2ay)
\(1,\left(x+2\right)\left(3x-4\right)=0\\ \Rightarrow\left[{}\begin{matrix}x+2=0\\3x-4=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=-2\\x=\dfrac{4}{3}\end{matrix}\right.\)
\(2,\dfrac{x-51}{9}+\dfrac{x-52}{8}=\dfrac{x-53}{7}+\dfrac{x-54}{6}\\ \Leftrightarrow\left(\dfrac{x-51}{9}-1\right)+\left(\dfrac{x-52}{8}-1\right)=\left(\dfrac{x-53}{7}-1\right)+\left(\dfrac{x-54}{6}-1\right)\\ \Leftrightarrow\dfrac{x-60}{9}+\dfrac{x-60}{8}-\dfrac{x-60}{7}-\dfrac{x-60}{6}=0\\ \Leftrightarrow\left(x-60\right)\left(\dfrac{1}{9}+\dfrac{1}{8}-\dfrac{1}{7}-\dfrac{1}{6}\right)=0\)
Vì \(\dfrac{1}{9}+\dfrac{1}{8}-\dfrac{1}{7}-\dfrac{1}{6}\ne0\Rightarrow x-60=0\Rightarrow x=60\)
3,ĐKXĐ:\(x\ne\pm2\)
\(\dfrac{x-2}{x+2}+\dfrac{3}{x-2}=\dfrac{x^2-11}{x^2-4}\\ \Leftrightarrow\left(x-2\right)^2+3\left(x+2\right)=x^2-11\\ \Leftrightarrow x^2-4x+4+3x+6-x^2+11=0\)
\(\Leftrightarrow-x+21=0\\ \Leftrightarrow-x=-21\\ \Leftrightarrow x=21\left(tm\right)\)
\(4,\dfrac{x^2+1}{2}=\dfrac{2x^2+x}{3}\\ \Leftrightarrow3\left(x^2+1\right)=2\left(2x^2+x\right)\\ \Leftrightarrow3x^2+3=4x^2+2x\\ \Leftrightarrow4x^2+2x-3x^2-3=0\\ \Leftrightarrow x^2+2x-3=0\\ \Leftrightarrow\left(x^2+3x\right)-\left(x+3\right)=0\\ \Leftrightarrow x\left(x+3\right)-\left(x+3\right)=0\\ \Leftrightarrow\left(x+3\right)\left(x-1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x+3=0\\x-1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-3\\x=1\end{matrix}\right.\)